Living together separately : Arabs and Jews in contemporary Jerusalem - Romann, Michael; Weingrod, Alex; Mekhon Yerushalayim le-ḥeḳer Yiśraʼel (Princeton, New Jersey : Princeton University Press, 1991)
Focusing on the conduct of everyday life, rather than ideology. provides a look at the complex networks of practical relations developed by Jews and Arabs in over two decades of Israel control of the city (cont.).
(Cont.) ... Adressing such questions as : how does the use of urban space and urban systems reflect both segregation and integration? how do ethnic identities influence interactions in adjoining neighborhoods, workplaces, etc.? (cont.).
(Cont.) in the final chapter the authors evaluate the Jerusalem situation in comparison with conditions in other deeply divided cities and in light of the Intifada.
Cover ; List of Maps and Tables; Preface; 1. Jerusalem between Past and Present.
"Written under the auspices of the Jerusalem Institute for Israel Studies."
Includes bibliographical references (pages 245-248) and index.
Print version record.
JSTOR
Keywords: Palestinian Arabs -- Jerusalem; Jews -- Jerusalem; Arab-Israeli conflict -- 1973-1993.; Jerusalem -- Ethnic relations; Palestiniens -- Jérusalem.; Juifs -- Jérusalem.; Relations judéo-arabes -- Histoire -- 1973-1993.; Jérusalem -- Relations interethniques; Conflit israélo-arabe -- 1973-1993.; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; SOCIAL SCIENCE -- Anthropology -- Cultural; Arab-Israeli conflict; Ethnic relations; Jews; Palestinian Arabs; Middle East -- Jerusalem; Araber; Juden; Palästinenser; Jerusalem; Politischer Konflikt; Separatismus; Soziale Integration; Joden; Palestijnen; Etnische betrekkingen; Relations Juifs-Arabes.; Juifs -- Jérusalem.; Palestiniens -- Jérusalem.; Conflit israélo-arabe -- 1973-1993.; Jérusalem -- Politique et gouvernement; Jérusalem -- Relations interethniques; Araber; Juden; 1973-1993; Jews; Arabs; Jerusalem (Israel)